Genes and proteins of Escherichia coli (GenProtEc). - Riley, M (1996)
GenProtEc is a database of Escherichia coli genes and their gene products, classified by type of function and physiological role and with citations to the literature for each. Also present are data on sequence similarities among E.coli proteins with PAM values, percent identity of amino acids, length of alignment and percent aligned. The database is available as a PKZip file by ftp from mbl.edu/pub/ecoli.exe. The program runs under MS-DOS on IMB-compatible machines. GenProtEc can also be accessed through the World Wide Web at URL http://mbl.edu/html/ecoli.html.